Amorphous calcium zinc phosphate promotes macrophage-driven alveolar bone regeneration via modulation of energy metabolism and mitochondrial homeostasis - Shuze Wang; Lei Cao; Caihao Huang; Junyi Wang; Jialin Liu; Yeyuan Wang; Qiang Wang; Qing Zhou; Xing Zhang; Dan Zhang (Bioactive Materials)
The repair of alveolar bone defects continues to pose a significant challenge within the field of stomatology. As the primary implant material utilized in clinical treatment, the mechanisms by which calcium phosphate-based materials promote bone formation necessitate further in-depth exploration. Single-cell RNA sequencing was employed to characterize the immune microenvironment surrounding hydroxyapatite (HA)-mediated alveolar bone regeneration, confirming the macrophage-dependent enhancement of regenerative outcomes. Based on this finding, amorphous calcium zinc phosphate (ACZP) nanoparticles were developed as immunomodulatory nanomaterials. ACZP can accelerate bone regeneration via anti-inflammatory phenotype polarization, specifically by inhibiting endoplasmic reticulum-mitochondria coupling, reducing pathological Ca2+ transfer, and shifting macrophage metabolism from glycolysis to oxidative phosphorylation (OXPHOS), thereby enhancing bioenergetics. Our results demonstrated that ACZP can inhibit the IP3R/MCU pathway in macrophages, restoring their anti-inflammatory capabilities and ultimately achieving significant effects in the alveolar bone defects of New Zealand white rabbits. Twelve weeks post-surgery, the defects in the ACZP group were filled with nearly 70 % newly formed bone tissue. This study elucidated the immunomodulatory role of ACZP materials in the dynamic process of alveolar bone healing, providing novel insights and methodologies for the design of materials in the fields of tissue engineering and regenerative medicine.